Perbedaan Kompetensi Interpersonal Antara Siswa Program Khusus Dengan Siswa Regular Di SMP Batik Program Khusus Surakarta Dan Smp Batik Surakarta Tahun 2016/2017 - Kidung, Ananta; , Drs. Djumali, M.Pd (2016)
The purpose of this reserach are: 1) The difference between the student interpersonal competence with the Special Programme Regular students in junior high school and junior Batik Batik Surakarta Surakarta Special Program 2016/2017 academic year. 2) Comparing the level of interpersonal competence special and regular program students in junior high school and junior high school Special Program Batik Surakarta. 3) The level of interpersonal competencies students Special Programs. 4) The level of regular student interpersonal competence. This includes comparative quantitative research to draw conclusions through statistical analysis. The population in this study were all students of class VIII SMP Batik Surakarta and eighth grade students of SMP Batik Special Programme Surakarta academic year 2016/2017. Samples taken are as many as 84 students with a basis for taking proportional random sampling technique. Necessary data obtained through questionnaires and documentation. Questionnaire earlier in tested and test validity and reliability. Data analysis technique used was T test two samples with 21:00 SPSS for windows. The results showed that there is a difference between junior high school students in a special program Batik Surakarta Special Program with students who take regular courses in junior Batik Surakarta. Students who study Special Programme has a mean of 153.05 while students who study in regular program had a mean of 137,41 a significance level of 0.002 (P <0.05) based on the results of the hypothesis is accepted or proven.